Restricted streptomycin use in apple orchards did not adversely alter the soil bacteria communities - Walsh, Fiona; Smith, Daniel P.; Owens, Sarah M.; Duffy, Brion; Frey, Juerg E. (Frontiers in Microbiology, 2014)
Streptomycin has been authorized for restricted use in the prevention of the fire blight disease of pome fruit orchards in the EU and Switzerland. This study addresses the important topic of the influence of the use of streptomycin in agriculture on the total bacteria community within the soil ecosystem. Soil samples were taken from soils under apple trees, prior to streptomycin application and two weeks post streptomycin application or water application (untreated control). High throughput 16S rRNA gene amplicon sequencing was used to generate datasets from the soils under apple trees in apple orchards from three different locations in Switzerland. We hypothesized that the use of streptomycin would reduce the bacterial diversity within the soil samples and enhance a reduction in the variety of taxa present. Bacterial species such as Pseudomonas, Burkholderia and Stenotrophomonas are intrinsically resistant to many antibiotics and as such it is of interest to investigate if the use of streptomycin provided a selective advantage for these bacteria in the soil ecosystem. The application of streptomycin did not influence the abundance and diversities of major bacteria taxa of the soils or the Pseudomonas, Burkholderia and Stenotrophomonas species. We also discovered that apple orchards under the same management practices, did not harbor the same bacterial communities. The restricted application of streptomycin in the protection of apple orchards from the fire blight pathogen Erwinia amylovora under the guidelines in Switzerland did not alter either the bacterial diversity or abundance within these soil ecosystems.